You are on page 1of 6

# FUNCTIONS: Set of ordered pairs of real numbers (x, y) in which no two distinct ordered pairs have the same

## first coordinate. (Meaning: x values can never repeat)

-

Passes the vertical line test - where the graph and the line should only intersect at one point Ex

A Function

Not a Function

1. Linear

A line is formed by connecting two points General form: ax + y + c = 0 Standard form: y = mx + b where m = slope of the line & b = y intercept Domain: All real numbers Range: All real numbers

Slope :

m=

D=

## To get the equation of the line:

Point-slope form:

Two-point form:

## line Form: y=b

General form: ax2+bx+c=0 where a, b, c Real Numbers and a 0 Standard form: y= (x-h)2+k where Vertex(h, k) Domain: all real numbers

Range: For parabolas facing upward: [k, +) For parabolas facing downward: (-, k]

Standard form: y = Domain: r2- (x-h)20

+k

Range: For (+) semi circle: [k, k+r] (-) semi circle: [-r+k, k]

4. Absolute value Standard form: y = |x-h|+k Domain: all real numbers Range: dependent on k and where the graph is facing

5. Rational Function

General Form:

Domain: all real numbers except any x value that will make Q (x) = 0 Range: * see the graph

o

## Values of x that will make the denominator equal to zero

2.) Find the horizontal asymptotes o If degree of P(x)> Q(x), then no H.A.
o

## If degree of P(x) = Q(x), then H.A. is

o If degree of P(x) < Q(x), then H.A is y = 0 3.) Plot the asymptotes and test points. Then, graph.

6. Piecewise Combination of everything Domain: dependent on the domains specified in each part

I.

## ODD & EVEN Functions:

Even if f(-x) = f (x) or symmetric along y-axis Odd, if f(-x) = -f(x) or symmetric along x-axis and passes through the origin * y = 0 is a function that is both odd and even

II.

o

f (x) f-1(x)

Ex

f(x) = 5x+4

f-1(x) = (x-4)/5

## Domain f(x) = Range f-1(x) Range f(x) = Domain f-1(x)

III.

Operations on Functions A. (f+g) (x) = f(x) + g(x) B. (f-g) (x) = f(x) g(x) C. (fg) (x) = f(x) g(x) D. (f/g) (x) = f(x) / g(x) E. (fg) (x) = f(g(x))

* (f f-1) (x) = x